Makna Zikir Bagi Jemaah Tarekat NaqshabandÄ«yah KhÄlÄ«dÄ«yah Majelis Pengkajian Tauhid Tasawuf Indonesia di Kota Gorontalo - Rahmawati, Rahmawati; Yahiji, Kasim; Mustakimah, Mustakimah (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2018)
This article attempts to elaborate the existence of dhikr along with its meaning performed and hold by the members of the Majelis Pengkajian Tauhid Tasawuf Indonesia under the auspices of the Tarekat Naqshaband?yah Kh?lid?yah in Gorontalo City. The study indicates that dhikr is a substantially mandatory ritual that must be performed by the followers of the tarekat. In this point they interpret the meaning of dhikr within various arguments. The tarekat members who reached what so-called the level of tawh?d ?aq?dah argue that dhikr is an important matter which brings about positive energy and leads its performers to discover true religious spirituality. They believe that the positive energy becomes significantly determinant factor and it has relevance to solve the problems of daily life. On the other side, the tarekat members who have reached the level of taw??d ??fi interpret dhikr as a spiritual obligation which orients its performers to lovingness and intimacy with God. To the urban society of Gorontalo dhikr is viewed as a mindset which emphasizes that within spiritually sacred realm, on one hand, dhikr provides a positive indication which is coherently compatible with the profane reality of their life on the other.